2006
DOI: 10.1521/jscp.2006.25.6.647
|View full text |Cite
|
Sign up to set email alerts
|

Blame for Intimate Partner Violence: An Attributional Analysis

Abstract: El sexismo del observador y el comportamiento de la mujer han demostrado su influencia sobre el modo en que las personas juzgan a esta última cuando es agredida físicamente por su pareja. Con el fin de averiguar cómo influye la interacción de ambos factores sobre la atribución de culpa a la mujer víctima de violencia de pareja, se expuso a 120 participantes a viñetas experimentales, previa medición de sus niveles de sexismo benevolente y hostil. Los resultados mostraron que los sexistas benevolentes culpaban a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 23 publications
2
46
1
3
Order By: Relevance
“…For instance, several studies have found that male observers generally report more tolerant attitudes or perceptions of violent behavior relative to female observers (e.g., Bryant and Spencer 2003;Cook and Harris 1995;Locke and Richman 1999). Furthermore, observer gender has been shown to interact with victim confrontation (e.g., Leigh and Aramburu 1994;Pierce and Harris 1993;Witte et al 2006), such that male observers often blame female victims more in cases of confrontation relative to female observers. Female observers, on the other hand, have been shown to assign high levels of responsibility and blame to male perpetrators, irrespective of victim confrontation.…”
Section: Effect Of Observer Gender On Attributions Of Blame and Respomentioning
confidence: 99%
“…For instance, several studies have found that male observers generally report more tolerant attitudes or perceptions of violent behavior relative to female observers (e.g., Bryant and Spencer 2003;Cook and Harris 1995;Locke and Richman 1999). Furthermore, observer gender has been shown to interact with victim confrontation (e.g., Leigh and Aramburu 1994;Pierce and Harris 1993;Witte et al 2006), such that male observers often blame female victims more in cases of confrontation relative to female observers. Female observers, on the other hand, have been shown to assign high levels of responsibility and blame to male perpetrators, irrespective of victim confrontation.…”
Section: Effect Of Observer Gender On Attributions Of Blame and Respomentioning
confidence: 99%
“…Also shown to increase levels of blame are intimacy level of the relationship (dating vs. married; Langhinrichsen-Rohling et al, 2004;Willis et al, 1996), suggesting that women who are unmarried are blamed more than those women who are married; provocation by the victim (Harris & Cook, 1994;Pierce & Harris, 1993), where women who have done something to "provoke" the batterer are blamed more than those who did nothing to initiate the violence; and the victim's reaction to the abuse (Capezza & Arriaga, 2008), where women who do something to retaliate (such as yelling) are blamed at greater rates as well. Finally, severity of violence has shown to increase the amount of blame attributed to the abuser and decrease the blame placed on the survivor (Lane & Knowles, 2000;Pierce & Harris, 1993;Reddy et al, 1997;Witte, Schroeder, & Lohr, 2006). Following is an in-depth review of studies examining the influence of these factors on attributions of blame toward women who have been battered, as well as their methodological strengths and limitations.…”
Section: Perceptions Of Women Who Have Been Batteredmentioning
confidence: 99%
“…Adding additional victim behavior variables, Witte et al (2006) sought to determine the effects of the victims' behavior, expectations about the perpetrator, severity of violence, and observer gender on attributions of IPV. They hypothesized that participants would view the victim as a cause for the assault based on her behavior prior to the violence, and therefore attribute greater blame to the victim than the perpetrator based on traditional theories of attribution (Jones & McGillis, 1976;Kelly, 1971b).…”
Section: Witte Et Al (2006)mentioning
confidence: 99%
See 2 more Smart Citations